Heterometallic 3d–4f Complexes as Single‐Molecule Magnets. Issue 24 (23rd August 2019) - Dey, Atanu; Acharya, Joydev; Chandrasekhar, Vadapalli
Abstract: Heterometallic 3d‐4f complexes are being investigated, for some time, as being useful in molecular magnetism, particularly as single‐molecule magnets (SMMs). This interest is primarily because of the possibility of an increased ligand‐mediated super‐exchange phenomenon between the 3d and 4f metal ions. Such an interaction, apart from bestowing a favorable ground‐state spin to the complex, also assists in reducing quantum tunneling of magnetization that is widely prevalent in SMMs making them to lose magnetization. However, assembling both 3d as well as 4f ions using same ligand system is challenging and involves the design of multi‐site coordination ligands with specific coordination compartments for the 3d and the 4f metal ions while at the same time allowing these disparate metal ions to be linked to each other through a bridging ligating atom. This review presents a summary of the 3d‐4f complexes primarily derived from the author's work while alluding to important examples from the literature. We also provide an outlook for the future design of such complexes. Abstract : Having a magnetic personality : In view of the recent advances in the field of heterometallic single‐molecule magnets (SMMs), this review presents 3d‐4f complexes as SMMs. The review is mainly based on the author's work along with some notable examples from the literature.